Nephrogenic Adenoma of Bladder—An Unusual Mimicker of Malignancy - Sajitha, Kaliyath; Kishan, Prasad Hosapatna Laxminarayana; Pai, Narendra; Bhat, Shubha P (Journal of Health and Allied Sciences NU, 2022)
Nephrogenic adenoma also referred to as nephrogenic metaplasia is a rare benign condition occurring most frequently in the urinary bladder. It is most commonly associated with chronic inflammation and genitourinary trauma and can present with a broad spectrum of histological features. It must be differentiated from malignant lesions, which can mimic both at cystoscopy and microscopically. Here, we report a case of nephrogenic adenoma in a middle-aged male with predisposing factors.
Keywords: nephrogenic adenoma; metaplasia; adenocarcinoma; mimicker